Determination of α- and β-acids in hops by liquid chromatography or electromigration techniques: A critical review. (15th December 2022) - Duarte, Lucas Mattos; Aredes, Rafaella Silva; Amorim, Tatiane Lima; de Carvalho Marques, Flávia Ferreira; de Oliveira, Marcone Augusto Leal
Graphical abstract: Highlights: Hop is an important ingredient for brewing mainly due to its bitterness and aromatic flavor features. Humulones and Lupulones, also known as - and -acids, are some of the most valuable hop compounds. High performance liquid chromatography is the most used separation technique for bitter acids determination. Capillary electrophoresis has emerged as a faster and greener alternative to chromatography for bitter acids determination. Analytical methods for hop acids determination, by LC and CE, are summarized and discussed. Abstract: Hop plays an essential role in brewing beer and its study and analysis is of paramount importance. - and -acids are considered two of the most important hop components. While -acids are associated with the bitter flavor, -acids have antimicrobial effects. This work aims to critically review the published analytical methods for - and -acids determination in hops employing separation methods in liquid medium: liquid chromatography (LC) and capillary electrophoresis (CE). The types of hop samples, the optimized protocols to extract the hop acids, and the main instrumental conditions for both LC and CE techniques are highlighted and discussed. Specific and critical aspects of the - and β-acids separation by LC and CE and some challenges in this field are raised. Several key aspects discussed in this review may be of practical importance for brewers, whether in the microbrewery or industry and for researchers in the brewing field.